TINJAUAN YURIDIS TERHADAP PERLINDUNGAN ANAK DALAM PERSPEKTIF HAK ASASI MANUSIA DI INDONESIA - Sally Dian Nastity; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2021)
The study's goal is to look at legal protection for children from a human rights standpoint. According to the findings, bullying in the form of physical, psychological, and sexual violence continues to be the most common kind of violation of children's rights. This research adopts the literature research method to collect relevant legal materials Children's legal protection is a barometer of a country's civilization. Human rights breaches include ignoring children's rights. Child protection refers to any efforts intended to ensure and protect children's rights so that they can live, grow, develop, and contribute to their full potential in a manner that is consistent with human dignity.In terms of human rights, how can the law be enforced against children? The goal of law enforcement is to provide victims with legal certainty and to prevent harm against minors. There are laws in Indonesia that control child protection. There are laws in Indonesia that control child protection, such as Law 35 of 2014 on Amendments to Law 23 of 2002 Concerning Child Protection., such as Law 35 of 2014 on Amendments to Law 23 of 2002 Concerning Child Protection. Legal arrangements on children's rights, such as the Convention on the Rights of the Child and Law Number 35 of 2014, should be even more assertive in terms of implementation and sanctions if a government collapses in enforcing them so that the current irregularity in the enforcement of legal arrangements on children's rights in various fields can gradually be stabilized.